Past Child Abuse and Neglect in Adults From Northern Mexico: Development of a Scale and Prevalence - Esparza-Del Villar, Oscar Armando (Journal of interpersonal violence, 2022)
Child abuse has been present in Mexico but there have been few studies that analyze its effects in adults. There are no Mexican validated scales that measure the relationship between abuse experienced in childhood and its effects into adulthood. The purpose of this study is to develop a past child abuse and neglect scale to measure these phenomena in adults and also to analyze the relationship the effects have with other psychological variables (e.g., anxiety, depression, self-esteem, partner-violence, personality, and fatalism). There were 763 participants from Juarez City, located on the northern border of Mexico. All participants were above the age of 18 years. The scale was developed, and its psychometric properties were analyzed. A first analysis consisted of analyzing the factor structure of the scale items with an Exploratory Factor Analysis (EFA), and then a Confirmatory Factor Analysis (CFA) was used to corroborate the factor structure. The resulting factors were guilt, relationship with parents, strong physical abuse, sexual abuse, mild physical and verbal abuse, and basic care. The internal reliabilities for all factors in both analyses were between Cronbach’s alpha values of .77 and .92. Correlations of these factors with psychological variables were analyzed, and several statistically significant correlations were found. The scale has a good factor structure that correctly reflects the indicators of child abuse and neglect with good internal reliability values. The analysis showed that the prevalence rates of child abuse and neglect in Juarez were higher than those reported by the World Health Organization (WHO) in other locations worldwide. Actions by governments, universities, and civil associations should take place to reduce these rates, especially because of their long-term physical, emotional, and psychological consequences.